The effects of the corona shock on the banking sector and the real economy - Johannes Pöschl (Danmarks Nationalbank, 2020)
This economic memo isolates two channels through which the "corona shock" affects the economy: a fall in asset prices and an increase in the dispersion of future shocks to the economy. Both shocks are contractionary, but they operate through different channels. A CCyB that is reactivated early reduces the impact of an asset price shock the most. In contrast, a CCyB that is reactivated late reduces the impact of a volatility shock the most.
Keywords: 330; Coronavirus; Schock; Wirkungsanalyse; Bank; Finanzmarktaufsicht